2021
DOI: 10.3390/nano11092373
|View full text |Cite
|
Sign up to set email alerts
|

High Q Resonant Sb2S3-Lithium Niobate Metasurface for Active Nanophotonics

Abstract: Phase change materials (PCMs) are attracting more and more attentions as enabling materials for tunable nanophotonics. They can be processed into functional photonic devices through customized laser writing, providing great flexibility for fabrication and reconfiguration. Lithium Niobate (LN) has excellent nonlinear and electro-optical properties, but is difficult to process, which limits its application in nanophotonic devices. In this paper, we combine the emerging low-loss phase change material Sb2S3 with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…As the phase transition to full crystallinity, the effective dielectric constant of chalcogenide PCM depends on the crystalline fraction m according to the Lorenz-Lorentz relation 49,52,68 , Based on the results on the dynamic nanoprinting and holographic image displays, it is confirmed that the phase-change metasurfaces offer an excellent platform to achieve the complete wavefront modulation across amplitude and phase spaces and dynamic multifunctionalities. In terms of information transmission, such a design provides the abundant degrees of freedom for a wide variety of applications associated with optical information encryption.…”
Section: Resultsmentioning
confidence: 84%
“…As the phase transition to full crystallinity, the effective dielectric constant of chalcogenide PCM depends on the crystalline fraction m according to the Lorenz-Lorentz relation 49,52,68 , Based on the results on the dynamic nanoprinting and holographic image displays, it is confirmed that the phase-change metasurfaces offer an excellent platform to achieve the complete wavefront modulation across amplitude and phase spaces and dynamic multifunctionalities. In terms of information transmission, such a design provides the abundant degrees of freedom for a wide variety of applications associated with optical information encryption.…”
Section: Resultsmentioning
confidence: 84%
“…Figure 5 explains a chronological graph showing various PCM based platforms explored for tunable nanophotonic applications from UV to THz. This include PCMs such as gallium lanthanum sulfide GL, 47 Ge 2 Sb 2 Te 5 (GST) in near-IR (NIR), 48 , 49 , 50 , 51 , 52 GST in mid-IR (MIR) to THz, 22 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 GST in visible (VIS), 20 , 21 , 66 Ge 3 Sb 2 Te 6 in MIR, 67 , 68 Ge 3 Sb 2 Te 6 in NIR, 69 Ge 2 Sb 2 Se 4 Te 1 (GSST) in MIR, 70 GSST in NIR, 71 , 72 , 73 , 74 , 75 GST in VIS to NIR, 76 , 77 , 78 bismuth telluride (Bi:Te) in the VIS, 79 Sb 2 S 3 in the VIS to NIR, 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 Sb 2 Se 3 in the VIS to NIR. …”
Section: Introductionmentioning
confidence: 99%
“… 130 (C) Scheme of the resonant Sb 2 S 3 -LN metasurface with a pair of Au electrodes, with the reflection spectra showing the tunability and the shift of the plasmon resonance with different gate voltage from 0 V to 200 V. Adapted from. 84 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study has focused on “customized” sub‐wavelength refractive index gratings consisting of periodic distributions of amorphous and crystalline PCMs, which can be “written,” “erased,” or “rewritten” by a tailored writing beam (laser or ion beam); [ 94 ] the geometric parameters (such as the structural period and duty cycle) can be modulated by controlling the excitation of the GMR [ 95 ] (Figure 7d). As the duty cycle decreases, the resonance wavelength is blue‐shifted, and the resonance peak, effective refractive index of the phase change layer, and absorption losses are reduced, resulting in a blue‐shift of the GMR and an increase in the Q‐factor.…”
Section: Mechanisms Of Color Changementioning
confidence: 99%